2020
DOI: 10.1101/2020.10.27.20219436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood asthma outcomes during the COVID-19 pandemic: Findings from the PeARL multi-national cohort

Abstract: Objective: We evaluated the impact of COVID-19 pandemic on childhood asthma outcomes. Design: The PeARL multinational cohort included children with asthma and non-asthmatic controls recruited during the COVID-19 pandemic and compared current disease activity with data available from the previous year. Setting: Pediatric outpatient clinics. Participants: The study included 1,054 children with asthma and 505 non-asthmatic controls, aged between 4-18 years, from 25 pediatric departments, from 15 countries globall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Recent large studies focusing on the course of asthmatic children during the pandemic revealed that they are not disproportionately affected by the virus, and surprisingly, they appear to have improved outcomes [15]. This was attributed to reduced exposure to asthma triggers, increased steroid prescriptions, and better treatment adherence during the pandemic.…”
Section: Why Asthmatic Children Were Initially Thought To Have a Gloomy Outcome During The Pandemicmentioning
confidence: 99%
“…Recent large studies focusing on the course of asthmatic children during the pandemic revealed that they are not disproportionately affected by the virus, and surprisingly, they appear to have improved outcomes [15]. This was attributed to reduced exposure to asthma triggers, increased steroid prescriptions, and better treatment adherence during the pandemic.…”
Section: Why Asthmatic Children Were Initially Thought To Have a Gloomy Outcome During The Pandemicmentioning
confidence: 99%
“…As such, the improved air quality may have helped stabilize the condition of asthma patients and reduce the frequency of AE. This is also affirmed by one multinational cohort study involving 1,054 children with asthma, showing that the outcomes of childhood asthma improved during the pandemic (18). Furthermore, research in the US and UK has shown a marked reduction in emergency visits by asthma patients during the pandemic (19,35).…”
Section: Discussionmentioning
confidence: 79%
“…As asthma and COPD exacerbations can both be triggered by respiratory infections and air pollution, among others (12,17), COVID-19 and its resulting social isolation measures may have had effects on chronic airway disease patients in several ways. Since previous studies have indicated that patients with asthma or COPD experienced improved disease control during the pandemic due to behavioral changes (18)(19)(20)(21), we hypothesized that the COVID-19 pandemic would confer an impact on the conditions of chronic respiratory diseases patients. Therefore, the present study aimed to compare the differences in clinical characteristics before and during the pandemic between asthma and COPD patients to analyze their risk factors for acute exacerbations (AEs) during the pandemic, and further to develop management strategies for chronic airway disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, improved or unchanged asthma control during pandemic was reported by 90.2% of the participants to a multi-national cohort study including 1,054 children with asthma and 505 non-asthmatic children aged 4-18 years from 15 countries. These findings might be due to reduced exposure to outdoor asthma triggers, such as seasonal allergens and air pollutants, and increased treatment adherence (38). Noteworthy, social distancing and facemasks have been proposed to reduce respiratory viral infection, leading to less hospital admission for asthma exacerbation in adults.…”
Section: Decreased Physical Activity and Increased Sedentary Behaviors In Asthmatic Children And Its Impact During The Covid-19 Pandemicmentioning
confidence: 99%